Cognitive Behavior Therapy to Reduce Irrational Beliefs in Schizophrenia Patients - Varina Citra Palupi; Meiyuntariningsih, Tatik (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study was motivated by the observation of a late adult who experienced schizophrenia. A person experiencing schizophrenia is required to take antipsychotic medication to reduce the positive and negative symptoms experienced, so they are expected to be compliant in taking the prescribed medication. The subjects in this study have shown irrational thoughts regarding the use of medication. The purpose of this study is to change the irrational thoughts that clients have related to the use of medication and the impact they have. This study used an experimental design in the form of single subject research with an A-B-A design. The data collection technique used in this study was to conduct behavioral measurements to assess whether the subject showed behavior in medication compliance. Data analysis used graphical techniques. The results show that the Cognitive Behavior Therapy (CBT) technique given is quite successful so that it can reduce irrational thoughts and bring up medication compliance behavior.